2016
DOI: 10.19044/esj.2016.v12n25p37
|View full text |Cite
|
Sign up to set email alerts
|

The Mediator Effect of Logistics Performance Index on the Relation Between Corruption Perception Index and Foreign Trade Volume

Abstract: Logistics performance of a country plays an important role within both economic and social developments. Therefore examining the relationship among the logistic performance, corruption and foreign trade volume of a country would contribute to the literature. Logistics Performance Index (LPI) has firstly been issued by World Bank in 2007 and continued in the years 2010, 2012, 2014. In this paper the mediator effect of Logistics Performance Index (LPI) on the relation between Corruption Perception Index (CPI) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 9 publications
2
12
0
Order By: Relevance
“…The LPI of importing countries has a positive significant impact on the export volume of foreign exporters. These results are consistent with previous studies [4,5,[33][34][35]. In addition, the LPI coefficient of exporting countries is higher than that of importing countries, indicating that the impact of LPI on the international trade of exporting countries is bigger than that for importing countries.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The LPI of importing countries has a positive significant impact on the export volume of foreign exporters. These results are consistent with previous studies [4,5,[33][34][35]. In addition, the LPI coefficient of exporting countries is higher than that of importing countries, indicating that the impact of LPI on the international trade of exporting countries is bigger than that for importing countries.…”
Section: Resultssupporting
confidence: 92%
“…Chakraborty and Mukherjee [34] researched the influence of LPI on export orientation and found that LPI has a significant positive impact on trade orientation. Using LPI as a moderator, Uca et al [35] found that LPI has a significant and positive impact on trade volume, and the moderating effect between corruption perceptions index and trade volume is statistically significant. Therefore, the first hypothesis is proposed: Hypothesis 1.…”
Section: Logistics Performance and International Tradementioning
confidence: 99%
“…This last hypothesis was also found significant meaning that the logistics ability of a country dominated the relationship between competitiveness and prosperity. Another study that applied hierarchical regression analysis was Uca et al (2016), which was similar to the previous one, but focused on the mediator effect of the LPI on the relationship between the Corruption Perception Index (CPI) and Foreign Trade Volume (FTV). The study, which was carried out in the same way as Civelek et al (2015), concluded that the logistics ability of a country triggers the relationship between corruption and foreign trade volume.…”
Section: Logistics Performance Index (Lpi)mentioning
confidence: 99%
“…There appear to be only a few such published studies, e.g. d' Aleo (2015), Guner and Coskun (2012), Koh et al (2018) and Uca et al (2016). Mateu (2017) suggests that gender diversity in the workplace enhances collaboration, tolerance, productivity and corporate social responsibility.…”
Section: Introductionmentioning
confidence: 99%